2021
DOI: 10.9798/kosham.2021.21.6.193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p-y Curves for Group Piles in Cohesive Soil Based on 3D Numerical Analysis

Abstract: The pile foundation supported on a structure can generate large horizontal loads due to earthquakes, high winds, and wave actions. The behavior of piles when subjected to horizontal load is generally analyzed using the p-y curve and “p-multiplier (Pm),” which is the coefficient of the group pile effect. In this study, the p-y curves and Pm were calculated by analyzing a single pile and group of piles arranged in 3 × 3 installed in cohesive soil using the finite element analysis program, Plaxis 3D. The soil res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In addition, the presence of interstitial water in the PB lattice is evidenced by the peaks appearing at 3252 cm −1 and 1610 cm −1 which correspond to the stretching and bending vibrations of O─H and H─O─H, respectively. [ 113,117,128 ] After the adsorption of PB, the FTIR spectra for Mo/Zr‐UiO‐66@PB reflected all the corresponding peaks of PB indicating the successful anchoring of the PB particles over the MOFs surface. Interestingly, in the FTIR spectra for Mo/Zr‐UiO‐66@PB, it can be observed that the peak corresponding to the vibrations of Fe─CN at 603 cm −1 is considerably reduced.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the presence of interstitial water in the PB lattice is evidenced by the peaks appearing at 3252 cm −1 and 1610 cm −1 which correspond to the stretching and bending vibrations of O─H and H─O─H, respectively. [ 113,117,128 ] After the adsorption of PB, the FTIR spectra for Mo/Zr‐UiO‐66@PB reflected all the corresponding peaks of PB indicating the successful anchoring of the PB particles over the MOFs surface. Interestingly, in the FTIR spectra for Mo/Zr‐UiO‐66@PB, it can be observed that the peak corresponding to the vibrations of Fe─CN at 603 cm −1 is considerably reduced.…”
Section: Resultsmentioning
confidence: 99%
“…These cations were selected for the study as they are the most commonly found cations in real groundwater and seawater, and could potentially compete during Pb 2+ /Cd 2+ uptake. [ 117 ] The interference study was conducted by mimicking the concentrations of the common cations found in seawater. The interference study was conducted for various concentrations of cations ranging from 0.1 mmol to 1 m .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations